The excavation of the temple of ʿAthtar dhu-Qabḍ in Barāqish. Stratigraphic data and historical reconstruction - Agostini, Alessio (Proceedings of the Seminar for Arabian Studies, 2015)
Excavations conducted by the Italian Archaeological Mission on the site of Barāqish (ancient Minaean Yathill) between 2004 and 2006 were able to unearth a massive hypostyle temple dedicated to the supreme Minaean divinity c Athtar dhu-Qabçl. The present article aims to reassess some of the preliminary results of these campaigns. The most significant architectonic features of this Minaean temple are outlined here, also emphasizing relevant similarities and differentiations between this building and the contiguous temple of Nakrah, excavated during the 1990s. Bigger dimensions, a six-pillared propylon, internal hall at a lower level and, possibly, the presence of an upper storey, are the more noteworthy features of this building. Some archaeological information obtained from the upper Islamic phases is also presented. These dense layers testify to the long and continuous occupation of the site from medieval to recent times. It is generally believed that these levels not only hid but also in some cases helped to protect the more ancient South Arabian ruins in this site. Finally, I will discuss two of the most complex phases of this building. The first concerns the circumstances of its foundation and its hypothetical dating to the end of the fourth century The second involves the period of abandonment following the fall of the Minaean kingdom (first century BC/AD), a phase that is still unclear, but which, according to this documentation, seems to have occurred only gradually.